2013
DOI: 10.1080/15374416.2013.844595
|View full text |Cite
|
Sign up to set email alerts
|

Relational Aggression in Middle Childhood Predicting Adolescent Social-Psychological Adjustment: The Role of Friendship Quality

Abstract: The present longitudinal study examined the indirect effect of 6th-grade negative friendship quality on the associations between 5th-grade relational aggression and age 15 social-psychological adjustment (i.e., depressive symptoms and risky behavior). The study consisted of a secondary analysis of the National Institute of Child Health and Human Development Study of Early Child Care and Youth Development using 776 children (M = 10.42 years in 5th grade; 50.4% boys) from the original sample. Using teacher and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 37 publications
0
21
0
1
Order By: Relevance
“…Typically, positive and negative provisions are (at best) only weakly correlated (Burk & Laursen, 2005;Furman, 1996;Mikami, Szwedo, Allen, Evans, & Hare, 2010;Wang, 2014), suggesting that they are independent relationship dimensions. Consistent with the notion that disruptive behaviours damage relationships over time, longitudinal studies indicate that externalizing symptoms foreshadow a degradation of friendship quality (e.g., Burk & Laursen, 2005;Kamper & Ostrov, 2013). For example, positive forms of friendship quality have been concurrently associated with lower levels of depression in second graders (Stocker, 1994) and with lower levels of anxiety in shy 10-year olds (Fordham & Stevenson-Hinde, 1999).…”
Section: Introductionmentioning
confidence: 83%
“…Typically, positive and negative provisions are (at best) only weakly correlated (Burk & Laursen, 2005;Furman, 1996;Mikami, Szwedo, Allen, Evans, & Hare, 2010;Wang, 2014), suggesting that they are independent relationship dimensions. Consistent with the notion that disruptive behaviours damage relationships over time, longitudinal studies indicate that externalizing symptoms foreshadow a degradation of friendship quality (e.g., Burk & Laursen, 2005;Kamper & Ostrov, 2013). For example, positive forms of friendship quality have been concurrently associated with lower levels of depression in second graders (Stocker, 1994) and with lower levels of anxiety in shy 10-year olds (Fordham & Stevenson-Hinde, 1999).…”
Section: Introductionmentioning
confidence: 83%
“…These youth may engage in relational aggression in the face of these challenges. In turn, engaging in relationally aggressive behaviors may be a risk factor for developing anxiety and depression because these behaviors interfere with the establishment of positive peer relationships (Kamper & Ostrov, 2013). Congruent with earlier research, early pubertal timing in the current study was associated with relational aggression (Hemphill et al, 2010; Sontag et al, 2011) and, in turn, relational aggression was associated with internalizing problems (Crick, 1996; see Murray-Close et al, 2016, for a review).…”
Section: Discussionmentioning
confidence: 99%
“…Given that problems with peer relationships have been found to be associated with internalizing problems (Laursen, Bukowski, Aunola, & Nurmi, 2007), theorists have suggested that internalizing problems may result from increased use of relational aggression due to these behaviors interfering with the establishment of positive peer relationships (e.g., Kamper & Ostrov, 2013; Murray-Close, Ostrov & Crick, 2007). There has been some evidence suggesting that the association between relational aggression and depressive symptoms is stronger for girls than for boys (Murray-Close et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has found that experiences of relational aggression and/or sexual harassment (both as victims and as perpetrators) are associated with a number of psychosocial adjustment concerns. These include externalizing behavioral problems such as antisocial behaviors (Bender & Losel, ), risk‐taking behaviors (Spieker et al, ), physical aggression (Crick, Ostrov, & Werner, ), and delinquency (Crick et al, ; Kamper & Ostrov, ; Sullivan, Farrell, & Kliewer, ), and internalizing behaviors such as difficulty with emotion regulation (Sullivan, Helms, Kliewer, & Goodman, ), depressive symptoms (Fite, Stoppelbein, Greening, & Preddy, ; Kawabata, Crick, & Hamaguchi, ; Spieker et al, ), and suicidal behavior (Fite et al, ; Winsper, Lereya, Zanarini, & Wolke, ). Given the deleterious outcomes associated with relational aggression and sexual harassment, it is important to understand factors that are associated with an increased likelihood of involvement in these behaviors.…”
Section: Associations Of Peer Influence With Relational Aggression Anmentioning
confidence: 99%